The concept of human resources and its relation to increased productivity accounting - Ostapenko, Natalia (My University, 2014)
The difficult economic situation in the country and radical changes in society have affected on one of the most important areas of society, which characterizes the efficiency of the economy - the labor resources of the country. Human resource management is of great importance, management of human resources, regulation, control of the labor potential, development of new methods to increase labor productivity.
Keywords: productivity; accounting; human resources; продуктивність; облік; людські ресурси; производительность; учет; людские ресурсы